(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Investigation of processing of dry-salted fish is described. The use of a satisfactory ratio of salt to fish, optimization of salting time and the use of mechanical driers to decrease drying time. The open sun stand and solar shelter drier were evaluated for their drying efficiency to assess the excellence of Stelophorusheterolobus and Sardinellagibbose. The highest mean temperature in the solar shelter drier was found to be 450 c, with relative humidity 42%, while in the open sun stand drying was 350 c, with relative humidity 47% at an air speed of 1.8 meter per second. The average moisture, crude protein, total lipids, free fatty acid, peroxide, total volatile basic nitrogen and ash constant of the solar shelter dried products were 7.5 %, 79.32%, 3.74%, 0.50%, 14.66%, 19.65% and 9.90%, and for open sun stand were7.7% 75.32%, 3.20%, 0.54%, 13.66%, 21.80% and 9.20%, respectively. Total plate count (TPC) of 3.2 × 103 cfu/g and 5.7 ×103 cfu/g was found within the average level for solar shelter and open sun stand driers respectively. Theexcellence of the fish products dried in the solar shelter drier was superior compared to that of open sun stand-dried products. It took only three days for the fish to be dried in the solar shelter drier compared with the open sun stand dried fish products which took five days to dry.